Morphological, phenotypical and molecular characterization of canine lymphomas with dual T- and B-cell markers expression - Mezzalira, Giorgia; Martini, Valeria; Abramo, Francesca; Iussich, Selina; Orlandi, Margherita; Pazzini, Luca; Banco, Barbara; Rambaldi, Anna Maria; Bisognoso, Alessandro; Arena, Filippo; Cocciolo, Giulio; Marino, Michele; et al. (Frontiers in Veterinary Science, 2025)
IntroductionRecent investigations have identified rare, phenotypically complex lymphoma variants, including cases exhibiting concurrent expression of T- and B-cell markers. These atypical presentations suggest perturbations in lymphoid differentiation programs or clonal evolution, necessitating more sophisticated diagnostic approaches. The concurrent expression of CD3 and CD20 in canine lymphomas represents a particularly compelling phenomenon documented across various anatomical sites. Molecular diagnostics, particularly PCR for Antigen Receptor Rearrangements (PARR), have provided crucial insights into these phenotypically complex cases, revealing concurrent clonal rearrangements of both TCRγ and IgH in selected cases, further challenging traditional classification paradigms.MethodsHere, we report 33 cases of canine double-positive lymphoma, retrieved with a retrospective analysis of the MyLAV Diagnostic Laboratory electronic database. Specifically, we report results of an integrated approach combining WHO-based morphological classification, comprehensive immunohistochemical immunophenotyping with T-cell (CD3 and CD5) and B-cell markers (CD20 and PAX5), and PARR analysis.ResultsThe skin, oral/nasal mucosa and mucocutaneous junction were the most commonly affected sites, accounting for 24 cases (72.7%). All cases stained positive for CD3 and CD20 (100%), 32 (97%) for CD5, and only 12 (36.4%) for PAX5. Aberrant cytoplasmic localization of CD20 was found in 29 (87.9%) cases. Molecular analysis revealed rearrangement signals of TCR gene in 23 of 33 cases (69.7%) and of CBmajor or CBminor gene in 9 (27.3%).DiscussionThe findings emphasize that while immunohistochemistry remains a fundamental diagnostic tool, it may be insufficient in isolation for definitive lineage determination in these cases. PARR analysis emerges as an essential complementary technique for distinguishing between aberrant marker expression and true biphenotypic differentiation.